José M. del Pino (ed.), George Ticknor y la fundación del hispanismo en Estados Unidos. Iberoamericana-Vervuert, Madrid-Frankfurt/M., 2022; 447 pp. - González Ramírez, David (El Colegio de México, 2024)
Review